2022
DOI: 10.3390/medicina58020285
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Candidate Genes for Major Depression

Abstract: Background and Objectives: The aim of this systematic review was to analyse which candidate genes were examined in genetic association studies and their association with major depressive disorder (MDD). Materials and Methods: We searched PUBMED for relevant studies published between 1 July 2012 and 31 March 2019, using combinations of keywords: “major depressive disorder” OR “major depression” AND “gene candidate”, “major depressive disorder” OR “major depression” AND “polymorphism”. Synthesis focused on asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 168 publications
0
6
0
Order By: Relevance
“…A multi-locus GWAS study demonstrated that several allelic variations in glutamatergic synaptic signaling, such as GRIK1, GRIK2, GRIK3, GRIN1, GRIN2A, GRIN2C or GRM7, were associated with MDD [77]. A subsequent systematic review revealed that several crucial candidate genes for MDD are involved in glutamate neurotransmission, [45]. Moreover, several studies found decreases in mRNA expression of NMDA and AMPA receptor subunits associated with schizophrenia in the frontal cortex [121][122][123].…”
Section: Functions Supported By Known Ppis Of Degsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-locus GWAS study demonstrated that several allelic variations in glutamatergic synaptic signaling, such as GRIK1, GRIK2, GRIK3, GRIN1, GRIN2A, GRIN2C or GRM7, were associated with MDD [77]. A subsequent systematic review revealed that several crucial candidate genes for MDD are involved in glutamate neurotransmission, [45]. Moreover, several studies found decreases in mRNA expression of NMDA and AMPA receptor subunits associated with schizophrenia in the frontal cortex [121][122][123].…”
Section: Functions Supported By Known Ppis Of Degsmentioning
confidence: 99%
“…Genetic variants of serotonergic, dopaminergic and adrenergic genes are the most extensively studied genes in relation to both depression and suicidal behavior; however, to date, only few candidate gene variants have been reliably associated with suicidality [43]. A recent meta-analysis identified novel depression-associated variants involved in the development and maintenance of cognitive processes [44]; moreover, a systematic review revealed that the most crucial candidate genes for major depressive disorder (MDD) are involved in glutamate neurotransmission, regulation of calcium channel activity and apoptosis [45]. A cell-type-specific methylome study pointed to the role of the innate immune responses via p75NTR/neurotrophic growth factor and Toll-like receptor signaling in MDD [46].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been of great interest to identify the specific determinants among such genetic influences, first in large general population samples and subsequently more narrowly defined smaller clinical samples. In this context, candidate gene studies have proposed a long list of common polymorphisms that are related to depressive disorders 19…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, genetic factors have been shown to play an important role in the development of both diseases. 5,6 Adenylate cyclase 3 (Adcy3) has been established as an important gene for both obesity and MDD, supported by both human [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and rodent [22][23][24][25][26][27][28] studies. 29 ADCY3 is a plasma membraneassociated protein that catalyzes the synthesis of cAMP, a secondary messenger that has itself been linked to the development and treatment of obesity and MDD.…”
Section: Introductionmentioning
confidence: 99%